DNA analysis for mysteries buried in history - Tanuj Kanchan; Kewal Krishan; Magdy A. Kharoshah (Egyptian Journal of Forensic Sciences, 2015)
Over the years DNA technology has proved to be a path breaking invention and this technological advancement in modern investigations will hopefully solve many more mysteries in the time to come. However, the developing world is lagging far behind owing to financial constraints and has resorted to relatively less reliable methods during investigations. Hopefully, developing nations too will follow suit in utilizing this technology to its potential.